2020
DOI: 10.1186/s13059-020-02146-5
|View full text |Cite
|
Sign up to set email alerts
|

Fine-tuning sugar content in strawberry

Abstract: Fine-tuning quantitative traits for continuous subtle phenotypes is highly advantageous. We engineer the highly conserved upstream open reading frame (uORF) of FvebZIPs1.1 in strawberry (Fragaria vesca), using base editor A3A-PBE. Seven novel alleles are generated. Sugar content of the homozygous T1 mutant lines is 33.9-83.6% higher than that of the wild-type. We also recover a series of transgene-free mutants with 35 novel genotypes containing a continuum of sugar content. All the novel genotypes could be imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(82 citation statements)
references
References 61 publications
2
79
0
1
Order By: Relevance
“…Moreover, CBEs are also promising tools for editing cis elements to fine‐tune gene expression. For example, increased sugar content in strawberry fruits was recently created with this approach (Xing et al ., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, CBEs are also promising tools for editing cis elements to fine‐tune gene expression. For example, increased sugar content in strawberry fruits was recently created with this approach (Xing et al ., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, CRISPR/Cas9-mediated deletion of the start codon site in a uORF of PHO1 improved inorganic orthophosphate tolerance in Arabidopsis (Reis et al, 2020). Another study reported that uORF editing of the FvebZIPs1.1 gene using a BE A3A-PBE system improved the sugar content in strawberries (Xing et al, 2020). Overall, many plant genes have been predicted to possess uORFs, and uORF editing is expected to become easier, owing to the availability of various CRISPR tools.…”
Section: Upstream Orf Editingmentioning
confidence: 99%
“…For example, editing of the uORF of LsGGP2 , which encodes an enzyme involved in vitamin C biosynthesis, using the CRISPR-Cas9 system conferred enhanced oxidative stress tolerance and elevated ascorbate levels [ 84 ]. In addition, editing the conserved uORF of FvebZIP1.1, which fine-tunes carbon–nitrogen metabolism, resulted in enhanced sugar content in strawberries compared to wild-type [ 85 ]…”
Section: Enhancing Gene Expression In Crops By Editing Uorfs Usingmentioning
confidence: 99%
“…For example, editing of the uORF of LsGGP2, which encodes an enzyme involved in vitamin C biosynthesis, using the CRISPR-Cas9 system conferred enhanced oxidative stress tolerance and elevated ascorbate levels [84]. In addition, editing the conserved uORF of FvebZIP1.1, which fine-tunes carbon-nitrogen metabolism, resulted in enhanced sugar content in strawberries compared to wild-type [85] Generally, elevated expression of stress-related genes inhibits plant growth due to the tradeoff between growth and defense. For example, overexpression of AtJMT in rice led to drought tolerance but decreased growth and yield [86].…”
Section: Enhancing Gene Expression In Crops By Editing Uorfs Using Thmentioning
confidence: 99%